2018
DOI: 10.5539/jas.v10n8p100
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Improved Hermetic Storage Structures Against Maize Storage Insect Pests Sitophilus zeamais and Prostephanus truncatus

Abstract: A study was conducted for 12 months to evaluate the effectiveness of two improved hermetic storage structures against two maize storage pests Sitophilus zeamais and Prostephanus truncatus at Liwufu Research Station, Malawi. The storages were metal silo and hermetic bag; Actellic super dust was included as a control. The treatments (storages) were replicated four times under natural and artificial infestations. Grain stored in metal silo had the lowest mean percentage weight loss, 1.04% to 1.25%, 12 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Polypropylene bags have been reported to be porous in nature and therefore allows for moisture absorption or loss unlike hermetic bags that have a restrictive gaseous inter change barrier [9]. Moisture content beyond 13% encourages microbial growth and favors mycotoxin development, implying that maize grains stored in polypropylene bags will be susceptible to microbial and aflatoxin contamination compared to those stored in hermetic bags [8]. Gasparin et al [10] and Bewley et al [11] reported that control of maize grain moisture is the surest way of sustaining its viability, quality and safety throughout stor age.…”
Section: Grain Quality Of Maize Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Polypropylene bags have been reported to be porous in nature and therefore allows for moisture absorption or loss unlike hermetic bags that have a restrictive gaseous inter change barrier [9]. Moisture content beyond 13% encourages microbial growth and favors mycotoxin development, implying that maize grains stored in polypropylene bags will be susceptible to microbial and aflatoxin contamination compared to those stored in hermetic bags [8]. Gasparin et al [10] and Bewley et al [11] reported that control of maize grain moisture is the surest way of sustaining its viability, quality and safety throughout stor age.…”
Section: Grain Quality Of Maize Samplesmentioning
confidence: 99%
“…Invasion of insects such as the maize weevil and the larger grain borer is responsible for such observation and was very profound in polypropylene bags due to its porous nature, permitting influx of oxygen for insect activity. These insects feed on maize endosperm leading to reduction in grain weight and end-product yield [8]. The lower insect damaged grains recorded in hermetic bags shows that it is better to store maize grains in hermetic bags than in polypropylene bags.…”
Section: Grain Quality Of Maize Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…A 50–80% germination drop in maize stored in uncontrolled warehouse after 8 months (about 32 weeks) has been documented in the USA (Tekrony et al ., 2005). Further, the rate of grain germination has been documented to differ with storage method used over time (Tefera et al ., 2018). However, the finding that the germination rate dropped for grain held in hermetic bags contrasts with other studies that showed seeds of all types stored in ultra-hermetic storage devices maintained high germination capacity (86.1%) (Villers, 2017).…”
Section: Discussionmentioning
confidence: 99%